PENGARUH REFERENCE GROUP DAN MARKETING MIX TERHADAP MINATMENGGUNAKAN PRODUK KJKS/BMT DI KOTA PEKALONGAN - AM. M. Hafidz MS.; Marlina; Sam'ani Sya'roni (JURNAL PENELITIAN, 2013)
This study was aimed to answer a question research: whether reference group and marketing mix influence the customers' interest in using the KJKS/BMT's products. To answer that question, quantitative approach was used. The population was BMT's customers of Pekalongan. Non-probability sampling technique (convenience sampling) was used to take samples of the population. There were 92 respondents that were used. The study concluded that based on t-test, it was known that the three independent variables: product, place, and promotion had significant effect on the customersí interest in using the BMT's products. While two others: price and reference group did not have significant effect. All variables, both the significant and not significant, had positive relationship with the dependent variable. They all had simultaneously significant effect on the dependent variable. The magnitude of the effect of independent variables on the dependent variable was 62.8 % as shown in figure Adjusted R2 in Regression Coefficient Test.